Trypanosoma brucei BRCA2 acts in a life cycle-specific genome stability process and dictates BRC repeat number-dependent RAD51 subnuclear dynamics - Trenaman, Anna (Oxford University Press, 2013)
Trypanosoma brucei survives in mammals through antigenic variation, which is driven by RAD51-directed homologous recombination of Variant Surface Glycoproteins (VSG) genes, most of which reside in a subtelomeric repository of >1000 silent genes. A key regulator of RAD51 is BRCA2, which in T. brucei contains a dramatic expansion of a motif that mediates interaction with RAD51, termed the BRC repeats. BRCA2 mutants were made in both tsetse fly-derived and mammal-derived T. brucei, and we show that BRCA2 loss has less impact on the health of the former. In addition, we find that genome instability, a hallmark of BRCA2 loss in other organisms, is only seen in mammal-derived T. brucei. By generating cells expressing BRCA2 variants with altered BRC repeat numbers, we show that the BRC repeat expansion is crucial for RAD51 subnuclear dynamics after DNA damage. Finally, we document surprisingly limited co-localization of BRCA2 and RAD51 in the T. brucei nucleus, and we show that BRCA2 mutants display aberrant cell division, revealing a function distinct from BRC-mediated RAD51 interaction. We propose that BRCA2 acts to maintain the huge VSG repository of T. brucei, and this function has necessitated the evolution of extensive RAD51 interaction via the BRC repeats, allowing re-localization of the recombinase to general genome damage when needed.